Soil mulch in control of soil temperature and incidence of weeds in the production of crisphead lettuce (Research, Society and Development, 2020)
It was evaluated the effects of different types of mulching of soil in the cultivation of crisphead lettuce (Lactuca sativa L.), cultivar “Lucy Brown”, in the spring period, on weed control, soil temperature and productivity. The experiment was arranged in a randomized block design with four treatments and five replications in plots of 14.0m2. The following coverages were studied: Pennisetum glaucum L., Avena strigosa, Brachiaria ruziziensis, plus the control treatment (soil without mulching). The use of mulching of soil, P. glaucum and B. ruziziensis, proved to be a beneficial practice, reducing the soil temperature by up to 5ºC. There was a lower incidence of weeds with the use of the P. glaucum and A. strigosa coverages. The use of mulch did not provide a significant gain in productivity, however, there was a gain regarding the quality of the product, since the coverage with P. glaucum provided an increase in the size of the head (fresh mass of the commercial head).